2000
DOI: 10.1063/1.373050
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion coefficient of polycrystalline silicon and silicon dioxide thin films at high temperatures

Abstract: The rapid growth of microelectromechanical systems ͑MEMS͒ industry has introduced a need for the characterization of thin film properties at all temperatures encountered during fabrication and application of the devices. A technique was developed to use MEMS test structures for the determination of the difference in thermal expansion coefficients ͑␣͒ between poly-Si and SiO 2 thin films at high temperatures. The test structure consists of multilayered cantilever beams, fabricated using standard photolithograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(93 citation statements)
references
References 16 publications
2
85
0
2
Order By: Relevance
“…The number of graphene layers are identified using This G band upshift is consistent with our previous work on suspended graphene, which showed a 25 cm -1 upshift in the supported region, while the suspended region remained constant after thermal cycling [30]. In this previous work, ripple formation in the suspended region of the graphene indicated that the G band upshift originated from the compression of the graphene lattice created by the mismatch of thermal expansion coefficients between the graphene and the underlying Si/SiO 2 substrate [18,19,31,32] 0.034 cm -1 /K. However, the Raman spectra observed before and after thermal cycling exhibit irreversible upshifts of the G band after the thermal cycle is complete, which must be taken into consideration when estimating the temperature coefficients of graphene.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The number of graphene layers are identified using This G band upshift is consistent with our previous work on suspended graphene, which showed a 25 cm -1 upshift in the supported region, while the suspended region remained constant after thermal cycling [30]. In this previous work, ripple formation in the suspended region of the graphene indicated that the G band upshift originated from the compression of the graphene lattice created by the mismatch of thermal expansion coefficients between the graphene and the underlying Si/SiO 2 substrate [18,19,31,32] 0.034 cm -1 /K. However, the Raman spectra observed before and after thermal cycling exhibit irreversible upshifts of the G band after the thermal cycle is complete, which must be taken into consideration when estimating the temperature coefficients of graphene.…”
supporting
confidence: 78%
“…In this previous work, ripple formation in the suspended region of the graphene indicated that the G band upshift originated from the compression of the graphene lattice created by the mismatch of thermal expansion coefficients between the graphene and the underlying Si/SiO 2 substrate [18,19,31,32]. In addition to compression, doping effects can also cause the G and 2D bands upshifts.…”
mentioning
confidence: 99%
“…At RT, SiO2 TEC is ~0.5 × 10 -6 K -1 , much smaller than that of monolayer MoS2 ~7 × 10 -6 K -1 , and increases with increasing temperature at a much smaller rate than MoS2. 38,39 Therefore, the strain in MoS2 film tends to accumulate with increasing temperature, and eventually goes beyond the confinement force of van der Waals bonding between the film and substrate, resulting in the change of the film morphology. Similar result has also been observed in graphene and WS2.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, with reducing temperatures, the intensity of the two-phonon mode (E 1g ) expands. This feature can be interpreted as when reducing the background signal from the two phonon procedure that increases the visibility of this peak and also the strain-instigated effects due to dissimilarity in thermal expansion coefficients of thinner films and substrate [84,85]. The frequency changes of two-phonon modes for monolayer, bilayers and bulk samples are plotted as a function of temperature ( Figure 7D), showing frequency jumps at 120 K, which also indicates the existence of the IC-CDW state in the thinner crystals of 2H-TaSe 2 .…”
Section: Temperature-dependent Resistivity and Magnetic Susceptibilitymentioning
confidence: 99%